2017
DOI: 10.1021/jacs.7b08803
|View full text |Cite
|
Sign up to set email alerts
|

Organocopper(III) Spiro Complexes: Synthesis, Structural Characterization, and Redox Transformation

Abstract: Reductive elimination of Cu(III) intermediates is often proposed as a key step in many copper-catalyzed or -mediated formation of C-C or C-heteroatom bonds. However, there still lacks concrete evidence on this key step, mainly because Cu(III) complexes are usually too unstable to be isolated and structurally characterized. In this work, novel organocopper(III) spiro complexes and their analogous organocopper(I) spiro complexes were synthesized and structurally characterized. Single-crystal X-ray structural ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 63 publications
0
33
0
Order By: Relevance
“…[13][14][15][16][17][18][19][20][21] However, Cu III complexes with well-defined structures remain rather limited and most reported examples were stabilized by rigid macrocyclic chelating ligands or perfluorinated groups, 18,[22][23][24][25][26] few of which provide experimental evidence for reductive elimination of Cu III species to form C-C or C-heteroatom bonds. [27][28][29] Seminal work by Stahl and Ribas have shown that a series of Cu III -mono-aryl species stabilized by an electrondonating macrocyclic ligand can undergo C-heteroatom bondforming reductive elimination reactions. The Xi group has recently reported a novel organocopper(III) spiro complex that can undergo intramolecular C-C bond-forming reductive elimination.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] However, Cu III complexes with well-defined structures remain rather limited and most reported examples were stabilized by rigid macrocyclic chelating ligands or perfluorinated groups, 18,[22][23][24][25][26] few of which provide experimental evidence for reductive elimination of Cu III species to form C-C or C-heteroatom bonds. [27][28][29] Seminal work by Stahl and Ribas have shown that a series of Cu III -mono-aryl species stabilized by an electrondonating macrocyclic ligand can undergo C-heteroatom bondforming reductive elimination reactions. The Xi group has recently reported a novel organocopper(III) spiro complex that can undergo intramolecular C-C bond-forming reductive elimination.…”
Section: Introductionmentioning
confidence: 99%
“…Later on it was shown, that direct salt elimination from 2,2′‐dilithiobiphenyl and boron halides resulted in 9‐halo‐9‐borafluorenes and derivatives . This method allowed synthesis of transition metal derivatives, too . Wagner successfully used silafluorenes as precursors for borafluorenes …”
Section: Introductionmentioning
confidence: 99%
“…Although neutral N,N-chelated spiro copper complexes are relatively common, the anionic C,N- or C,C-cheated spiro counterparts are sporadic. As mentioned above, Xi’s group found that the C,C-bidentate ligand is an excellent platform to build up diversified coordination complexes across the periodic table [ 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The chelating effect increases the thermal stability of these organometallic species, facilitating isolation and following characterization.…”
Section: Mononuclear Organocopper Complexesmentioning
confidence: 99%
“…Starting from the 1,4-dilithio 1,3-butadienes 1 (dilithio reagent for short) and 0.5 equiv. of copper(I) salts, Xi’s group isolated the first series of spiro organocopper(I) compounds 2–4 ( Scheme 2 ) [ 59 , 60 ]. It seems that the terminal alkenyl carbon atom is favorable for LiBr coordination, probably because it is more electron-rich than the phenyl ones.…”
Section: Mononuclear Organocopper Complexesmentioning
confidence: 99%